Buyer preferences for sheep and goats in southern Nigeria: A hedonic price analysis - Jabbar, M.A. (International Livestock Research Institute, 1998)
Nearly half of the small ruminants of the humid zone of Africa are found in Nigeria. As aggregate demand for small ruminant meat in the zone exceeds supply from local sources, the gap is met by supplies from the subhumid and semi-arid zones in the north of the country and beyond. In the past, only southern urban markets were served by northern animals, but in recent years, northern animals have started penetrating rural markets and their share has been increasing. This study seeks to determine if buyers of small ruminants in southern Nigeria have systematic preferences for specific species/breeds of small ruminants for specific purposes, and whether they pay significantly higher prices for different species/breeds consistent with their preferences. Answers to these questions have important implications for local and northern producers who supply the southern markets, albeit with different breeds.